2009
DOI: 10.1308/135576109787909463
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Orofacial Pain and Tooth Fracture (Odontocrexis) Associated with SCUBA Diving

Abstract: Among those who returned questionnaires, orofacial pain in divers was common and odontocrexis was rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Indeed, microleakage was detected in the zinc phosphate and glass‐ionomer cements after pressure cycling, whereas no microleakage was detected in the resin cement, 26 probably owing to dentinal tubule obstruction by resin tags or cement flexibility 27 . In the aforementioned survey of 125 Australian divers, no diver reported loosening of a crown or bridge occurring during diving 23 …”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, microleakage was detected in the zinc phosphate and glass‐ionomer cements after pressure cycling, whereas no microleakage was detected in the resin cement, 26 probably owing to dentinal tubule obstruction by resin tags or cement flexibility 27 . In the aforementioned survey of 125 Australian divers, no diver reported loosening of a crown or bridge occurring during diving 23 …”
Section: Introductionmentioning
confidence: 97%
“…These authors concluded that increased exposure to barometric stress was associated with elevated dental deterioration 22 . In a recent survey among 125 Australian divers, Jagger et al 23 reported one diver who experienced tooth shattering and two divers who experienced restoration displacement during diving. The authors concluded that dental barotrauma was uncommon and was reported by less than 1% of the divers 23 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations